СИНТЕЗ ЭЛЕКТРИЧЕСКОЙ СИСТЕМЫ ВО ВРЕМЕННОЙ ОБЛАСТИ МЕТОДОМ ПОИСКОВОЙ ОПТИМИЗАЦИИ - Ягуп, В.Г.; Ягуп, Е.В. (Інститут електродинаміки НАН України, Київ, 2015)
The synthesis problem of the electric system on time characteristic is solved by numerical method on Nelder-Meed algorithm. An efficiency function, which reflects difference between the prescribed time function and gotten one in the synthesized system, is subjected to minimization. Special feature of the method offered is use of maximally possible number of optimization parameters. The best topology of the synthesized system, providing tendency to decrease efficiency function to the infinitesimal quantity is brought out. The optimization results to any local minimum at the prescribed requirements of positiveness to the optimization parameters. Revaluation based on similarity theory is offered for transition to the real parameters. References 8, table 1, figures 4.